Comparative Analysis of Phraseological Units with Antonymous Components in English and Uzbek - Tursunova Zuhra; Rabiyeva Mohidil G'ayratovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
Abstract: Phraseological units with antonymous components represent a unique layer of linguistic expression where opposing semantic elements coexist within a stable, idiomatic structure to convey nuanced meanings, cultural values, and life’s inherent dualities. This study conducts a comparative analysis of such units in English and Uzbek, two genetically unrelated languages. It examines their structural types (binomial, proverbial, idiomatic contrasts), semantic classifications (temporal, moral/ethical, quantitative), and cultural reflections. The research reveals both universal cognitive patterns rooted in human experience and language-specific manifestations shaped by cultural contexts. Challenges in translation and equivalence are discussed, underscoring the role of these units in enriching stylistic expressiveness and cross-cultural understanding. Findings contribute to comparative phraseology and linguistic typology.